Pengaruh Destination Image Dan Fasilitas Wisata Terhadap Kepuasan Pelanggan Pada Wahana Wisata Di Lembah Tumpang - Safirah Haediyanti; Arni Utamaningsih; Baroroh Lestari (Jurnal Ekonomi dan Bisnis Digital, 2025)
East Java has a rich and diverse culture, including traditional art,dance,music and shadow puppet shows. Then for the purpose of recreation and tourism. This tourism is different from natural tourism which relies on the beauty and uniqueness. Therefore, this study aims to examine the effect of destination image and tourist facilities on customer satisfaction partially and simultaneously at the Tumpang Valley tourism resort in Malang Regency. This research uses a quantitative approach. The Data were obtained through observation, documentation and questionnaires. The Sampling using non- probability sampling with purposive sampling technique with a sample of 84 respondents. The distribution of the questionnaire was carried out offline (directly) to the people visiting the Tumpang Valley place in Malang Regency. Based on the results of the analysis, it showed that the Destination Image variable and Tourist Facilities have a positive and significant effect partially on the Customer Satisfaction variable. Meanwhile, the results of the analysis simultaneously also showed that Ho is rejected and h1 is accepted. It means that the Destination image variable and Tourist Facilities have a positive and significant effect simultaneously on the Customer Satisfaction variable. From the results of this study, it is recommended that Malang Regency Tumpang Valley Management increase innovation in developing tourist facilities and pay attention to customer satisfaction. This will be successful in increasing Customer Satisfaction in the place, and will ultimately support the sustainability of the tourist destination.